Control strategies for a hybrid renewable energy system: A review - Arul P.G.; Ramachandaramurthy V.K.; Rajkumar R.K. (Elsevier Ltd, 2023)
Power converters; Quality control; Renewable energy resources; Control strategies; Design and control; Grid connected systems; High quality power; Hybrid Renewable Energy System (HRES); Hybrid renewable energy systems; Renewable energy source; System stabilization; Electric power system control